Case report: The smallest 9p21.3 microdeletion involving CDKN2A but not CDKN2B causes multiple plexiform neurofibromas - Zhang, Yuanyuan; Li, Xiang; Gao, Haiming; Qiu, Chuang; Liu, Xiaoliang (Frontiers in Oncology, 2025)
Chromosome 9p21.3 is a locus associated with a rare autosomal dominant cancer predisposition syndrome characterized by early-onset melanoma and a broad spectrum of neural system tumors. Two major tumor-suppressor genes, cyclin-dependent kinase inhibitor 2A and 2B (CDKN2A and CDKN2B), as well as a large non-coding RNA ANRIL, are often co-deleted in the core region. Herein, we report a pregnant woman who had developed more than 20 plexiform neurofibromas since the age of 13 and experienced 11 times of surgical resections. No melanoma or other tumors were found. A germline 9p21.3 deletion involving CDKN2A and the first exon of ANRIL, but not CDKN2B, was identified by whole exome sequencing (WES) and confirmed by quantitative PCR. Prenatal diagnosis was performed through copy number variation-sequencing (CNV-seq), and the pregnancy was terminated with informed choice for an affected fetus. All the eight cases carrying germline 9p21.3 deletions were reviewed for genotype–phenotype correlation, showing that our case with the smallest deletion had plexiform neurofibroma only, and the two cases of Eastern Asian origin had no melanoma. Our data highlight 9p21.3 deletion as a potential differential diagnosis for neurofibroma and emphasize the importance of CNV analysis on the WES data wherein small deletions might be easily overlooked.